2015
DOI: 10.1504/ijbis.2015.069429
|View full text |Cite
|
Sign up to set email alerts
|

SMEs' adoption of e-commerce using social media in a Saudi Arabian context: a systematic literature review

Abstract: Through the analysis of a number of previous studies, this article aims to present an overview of extent literature on the adoption of e-commerce by Small and Medium-sized Enterprises (SMEs) using social media in a Saudi Arabian context. An extensive literature review has been grouped and represented in six different categories including information and Communications Technology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 57 publications
(37 reference statements)
1
23
0
Order By: Relevance
“…It has significant importance in marketing activities [43] which effect positively on the performance of organizations. Consistent with the current study, it is also evident that AISMM is also increasing among the Saudi Arabian SMEs [16]. Because AISMM has many advantages which push the companies to deal with these practices of marketing.…”
Section: In Relation To the Study's Aim And Objectivessupporting
confidence: 89%
See 2 more Smart Citations
“…It has significant importance in marketing activities [43] which effect positively on the performance of organizations. Consistent with the current study, it is also evident that AISMM is also increasing among the Saudi Arabian SMEs [16]. Because AISMM has many advantages which push the companies to deal with these practices of marketing.…”
Section: In Relation To the Study's Aim And Objectivessupporting
confidence: 89%
“…Saudi Arabian SMEs are facing different issues related to the marketing activities. Particularly, these companies are facing different problems related to the electronic commerce which is directly linked with social media marketing practices [16]. Moreover, Saudi Arabian SMEs facing the issues of human resource management [14] which has direct effect on all activities including social media marketing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…SNS can be used by organizations to reach customers (Lorenzo-Romero et al, 2011) and improve their relationship with customers (Su et al, 2015). Small and Medium Enterprises (SME) even use social media for e-commerce (Abed et al, 2015). In addition, SNS provide organizations a useful source of identifying potential employees (DeKay, 2009), and provide their employees' opportunities for online learning and education and improved interactivity.…”
Section: Authormentioning
confidence: 99%
“…Discarding both independent variables is a logical step as social commerce use does not need any technical infrastructure support as in system adoption; apart from the Internet cost, there is no monetary cost for using social media because most of the time, wireless connections are available free of charge. Thus, discarding the dependent variable use behaviour is because the literature indicated that social commerce technologies are new in the Arabian Gulf generally and in Saudi Arabia specifically and they are still not fully used [2]. The suggested constructs are demonstrated below in Table 1:…”
Section: Theoretical Basismentioning
confidence: 99%